Developing Phenomenological Sensitivity in Didactical Mathematics Through the Habit of Deep Observation in the Era of Industry 4.0 - ., Turmudi; Nunun, Nachipah (KnE Social Sciences, 2024)
A teacher needs to have the sensitivity in seeing didactic phenomena. The sensitivity can function as a vehicle or context for mathematics learning. The Konigsberg Bridge, for example, can be described without looking at the picture since it became a part of the community story. Later on, the description of the Konigsberg Bridge can be used as a context in mathematics learning, especially those related to Graph Theory. This paper discusses the phenomena such as the Konigsberg Bridge, to make mathematics teachers understand the didactic phenomena easily. By having the sensitivity of the mathematically valuable phenomena for the mathematics teachers, they can contribute more positively to mathematics education. Keywords: phenomenological sensitivity, didactical matchematics, habit of deep observation